Synthetic, Population-Based Virtual Patient Database Using a Digital Twin of the Cardiovascular System - Richárd Wéber; Márta Viharos; Benjamin Csippa; Dániel Gyürki; György Paál (Cardiovascular Engineering and Technology, 2026)
Purpose The goal is to develop a cardiovascular virtual patient database (VPD) combining physiological and demographic data to provide the foundation for future applications in medical diagnostics, decision-making, credibility testing, and formal uncertainty analysis, and to enable its integration with three-dimensional (3D) hemodynamic models and to train neural networks. Methods We generate an initial VPD by treating input parameters of a low-dimensional cardiovascular model as stochastic variables. Literature data and sensitivity analysis ensured physiological plausibility, while resampling improved physiological accuracy. Key physiological quantities are included such as systolic and diastolic aortic pressure, radial and carotid pressure, cardiac output, and diagnostic pulse wave velocities. Demographic factors (sex and age) are assigned based on their physiological impact. The open-source hemodynamic solver, first_blood, ensures accuracy and low computational time. Results The initial VPD consists of 50,000 Virtual Patients; after resampling, 34,347 remain in the final VPD. The difference of diastolic and systolic aortic pressures between the VPD ( $$70.24± 14.3$$ 70.24 ± 14.3 and $$116.8± 16.11$$ 116.8 ± 16.11 mmHg) and the literature ( $$75.6± 12.7$$ 75.6 ± 12.7 and $$113.0± 11.2$$ 113.0 ± 11.2 mmHg) is low. The differences caused by the sex of the patient are reproduced well by the VPD: increased diastolic aortic pressure for males ( $$72.1± 12.6$$ 72.1 ± 12.6 and $$68.5± 15.4$$ 68.5 ± 15.4 for males and females respectively). The VPD also accurately includes higher pulse wave velocities with age, patients below year 30 have $$6.3± 0.5$$ 6.3 ± 0.5 and above 70 have $$8.8± 1.2$$ 8.8 ± 1.2 m/s with a linear increment in-between. Conclusions The proposed methodology and first_blood solver effectively generate physiologically realistic virtual patient waveforms and demographic variability, providing a robust database for 3D cardiovascular simulations, machine-learning training datasets, and potential clinical decision support applications

Amplification of Secondary Flow at the Initiation Site of Intracranial Sidewall Aneurysms - Benjamin Csippa; Péter Friedrich; István Szikora; György Paál (Cardiovascular Engineering and Technology, 2025)
Purpose The initiation of intracranial aneurysms has long been studied, mainly by the evaluation of the wall shear stress field. However, the debate about the emergence of hemodynamic stimuli still persists. This paper builds on our previous hypothesis that secondary flows play an important role in the formation cascade by examining the relationship between flow physics and vessel geometry. Methods A composite evaluation framework was developed to analyze the simulated flow field in perpendicular cross-sections along the arterial centerline. The velocity field was decomposed into secondary flow components around the centerline in these cross-sections, allowing the direct comparison of the flow features with the geometrical parameters of the centerline. Qualitative and statistical analysis was performed to identify links between morphology, flow, and the formation site of the aneurysms. Results The normalized mean curvature and curvature peak were significantly higher in the aneurysmal bends than in other arterial bends. Similarly, a significant difference was found for the normalized mean velocity ( $$p=0.0274$$ p = 0.0274 ), the circumferential ( $$p=0.0029$$ p = 0.0029 ), and radial ( $$p=0.0057$$ p = 0.0057 ) velocity components between the arterial bends harboring the aneurysm than in other arterial bends. In contrast, the difference of means for the normalized axial velocity is insignificant ( $$p=0.1471$$ p = 0.1471 ). Conclusion Thirty cases with aneurysms located on the ICA were analyzed in the virtually reconstructed pre-aneurysmal state by an in-silico study. We found that sidewall aneurysm formation on the ICA is more probable in these arterial bends with the highest case-specific curvature, which are accompanied by the highest case-specific secondary flows (circumferential and radial velocity components) than in other bends.

Hydrodynamic Resistance of Intracranial Flow-Diverter Stents: Measurement Description and Data Evaluation - Benjamin Csippa; Dániel Gyürki; Gábor Závodszky; István Szikora; György Paál (Cardiovascular Engineering and Technology, 2020)
Purpose Intracranial aneurysms are malformations forming bulges on the walls of brain arteries. A flow diverter device is a fine braided wire structure used for the endovascular treatment of brain aneurysms. This work presents a rig and a protocol for the measurement of the hydrodynamic resistance of flow diverter stents. Hydrodynamic resistance is interpreted here as the pressure loss versus volumetric flow rate function through the mesh structure. The difficulty of the measurement is the very low flow rate range and the extreme sensitivity to contamination and disturbances. Methods Rigorous attention was paid to reproducibility, hence a strict protocol was designed to ensure controlled circumstances and accuracy. Somewhat unusually, the history of the development of the rig, including the pitfalls was included in the paper. In addition to the hydrodynamic resistance measurements, the geometrical properties—metallic surface area, pore density, deployed and unconstrained length and diameter—of the stent deployment were measured. Results Based on our evaluation method a confidence band can be determined for a given deployment scenario. Collectively analysing the hydrodynamic resistance and the geometric indices, a deeper understanding of an implantation can be obtained. Our results suggest that to correctly interpret the hydrodynamic resistance of a scenario, the deployment length has to be considered. To demonstrate the applicability of the measurement, as a pilot study the results of four intracranial flow diverter stents of two types and sizes have been reported in this work. The results of these measurements even on this small sample size provide valuable information on differences between stent types and deployment scenarios.

Multiple Aneurysms AnaTomy CHallenge 2018 (MATCH): Phase I: Segmentation - Philipp Berg; Samuel Voß; Sylvia Saalfeld; Gábor Janiga; Aslak W. Bergersen; Kristian Valen-Sendstad; Jan Bruening; Leonid Goubergrits; Andreas Spuler; Nicole M. Cancelliere; David A. Steinman; Vitor M. Pereira; et al. (Cardiovascular Engineering and Technology, 2018)